Urinary MCP-1 and VCAM-1 as non-invasive biomarkers for the diagnosis and activity assessment of lupus nephritis - Lichuan Lai; Chunle Wu; Xiaohua Li; Yuxiang Rong; Ying Huang; Bangqin Wang (PLoS ONE, 2025)
Introduction Accurate diagnosis of lupus nephritis (LN) and effective assessment of its disease activity are essential for optimal management. This study aimed to evaluate the potential of novel urinary biomarkers, MCP-1 and VCAM-1, in diagnosing and assessing LN activity, comparing their efficacy to traditional urinary biomarkers, and proposing a new standard for clinical application. Methods A total of 55 LN patients who met the 1997 ACR diagnostic criteria for systemic lupus erythematosus (SLE) and 34 healthy controls (HCs) were included in this study. The LN patients were categorized into two groups based on their SLE disease activity indices (SLEDAI): the inactive lupus nephritis (NALN) group (SLEDAI 0–4, n = 32) and the active lupus nephritis (ALN) group (renal SLEDAI ≥ 4, n = 22). Additionally, the patients were further classified into mild (SLEDAI 5–9), moderate (SLEDAI 10–14), and severe (SLEDAI > 14) subgroups. All LN patients underwent testing for urinary MCP-1 (uMCP-1), urinary VCAM-1 (uVCAM-1), urinary α1-microglobulin (u-α1MG), urinary β2-microglobulin (u-β2MG), urinary IgG (u-IgG), and urinary albumin (u-ALB), as well as a percutaneous renal biopsy. Results The levels of urinary MCP-1 and VCAM-1 (uMCP-1 and uVCAM-1) in the LN group were significantly elevated compared to the HCs (uMCP-1: P < 0.001; uVCAM-1: P < 0.01). Receiver operating characteristic (ROC) curve analysis revealed that the diagnostic efficacy of uMCP-1 and uVCAM-1 surpassed that of traditional biomarkers (uMCP-1: AUC = 0.79, P < 0.001; uVCAM-1: AUC = 0.77, P < 0.001). Multivariate logistic regression demonstrated a significant association between uMCP-1 and uVCAM-1 levels and the occurrence of LN (P < 0.001). Furthermore, these novel biomarkers exhibited stronger correlations with SLEDAI scores than traditional biomarkers (P < 0.001). Notably, patients with ALN had significantly higher levels of uMCP-1 and uVCAM-1 compared to those with NALN (uMCP-1: P < 0.01; uVCAM-1: P < 0.01). Conclusion The production of uMCP-1 and uVCAM-1 is closely associated with the onset and progression of LN (ISN/RPS: Class I - IV). These biomarkers may serve as valuable references for the diagnosis and prediction of LN and aid in the assessment of LN activity.